2011
DOI: 10.1007/s00296-011-1913-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SV40-transformed synovial fibroblasts in the study of rheumatoid arthritis pathogenesis

Abstract: The SV40 T antigen has been used to generate immortalized cells from rheumatoid arthritis (RA) synovial fibroblasts (RASFs) that are commonly used in lieu of primary RASFs. In the current study, we investigated the effect of stimulation by tissue necrosis factor alpha (TNF-α) and interleukin 17 (IL-17) on primary and immortalized RASFs in order to gauge the appropriateness of the use of immortalized RASFs, the MH7A cell line, in the study of RA pathogenesis. Changes in the levels of secretion and expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The ORs for subjective stress, sadness or despair, suicidal thoughts, suicide planning, and suicide attempts of the 2020 participants were compared with those of the 2019 participants using multiple logistic regression analysis with complex sampling using the weighted value of each participant. 21 Both the male and female groups showed lower odds of experiencing severe stress, sadness or despair, and suicidality in 2020 than in 2019 (Table 3). In the male group, the 2020 participants had lower odds of very severe stress (aOR, 0.68 [95% CI, 0.61-0.77], P < .001 ), sadness or despair (aOR, (ie, the high-, middle-, and low-income groups) showed lower odds of severe stress, sadness or despair, suicidal thoughts, and suicide attempts in the 2020 participants than in the 2019 participants (Table 4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ORs for subjective stress, sadness or despair, suicidal thoughts, suicide planning, and suicide attempts of the 2020 participants were compared with those of the 2019 participants using multiple logistic regression analysis with complex sampling using the weighted value of each participant. 21 Both the male and female groups showed lower odds of experiencing severe stress, sadness or despair, and suicidality in 2020 than in 2019 (Table 3). In the male group, the 2020 participants had lower odds of very severe stress (aOR, 0.68 [95% CI, 0.61-0.77], P < .001 ), sadness or despair (aOR, (ie, the high-, middle-, and low-income groups) showed lower odds of severe stress, sadness or despair, suicidal thoughts, and suicide attempts in the 2020 participants than in the 2019 participants (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…The ORs for subjective stress, sadness or despair, suicidal thoughts, suicide planning, and suicide attempts of the 2020 participants were compared with those of the 2019 participants using multiple logistic regression analysis with complex sampling using the weighted value of each participant. 21 Crude and adjusted models (for age, BMI, physical exercise, sedentary time for study and leisure, sleep time, sex, economic level, educational levels of the father and mother, scholastic performance, and subjective health status) were designed. Subgroup analyses by sex, economic level, and scholastic performance were designed.…”
Section: Methodsmentioning
confidence: 99%
“…[10] found that SV40 immortalized MEFs have significant resistance toward D, L-sulforaphane (SFN) induced apoptosis compared with wild-type MEFs. While SV40 Ta has been effective for immortalizing different cell types, many have cited molecular and phenotypic differences between wild type and SV40 transformed cell lines [11-15]. Jeong et al .…”
Section: Introductionmentioning
confidence: 99%
“…To further validate the ability of NP to serve as an effective treatment strategy for RA, in vitro experiments were also conducted with primary cells. Previous reports have noted discrepancies in cytokine production between cell line models and primary RASF cells [ 35 ]. Furthermore, a literature search revealed that immortalized cells, such as SW982, constitutively express the NF-κB pathway, indicating that they may be more susceptible to NF-κB interference than primary RASF cells [ 36 ].…”
Section: Resultsmentioning
confidence: 99%